Inhibition effects of thermally degraded MEG on hydrate formation for gas systems - AlHarooni, K.; Barifcani, Ahmed; Pack, David; Gubner, Rolf; Ghodkay, Varun (2015)
© 2015 Elsevier B.V. Mono-ethylene glycol (MEG) is used as a hydrate inhibitor in gas processing plants and transportation pipelines. Due to its high cost, large consumption rate, and its environmental impact, regenerating MEG is an economical and environmental solution. When heated to high temperatures at the reboiler, thermal degradation of MEG may occur during the regenerating process. In this work, the hydrate inhibition performance of MEG after it was thermally exposed to high temperatures has been evaluated. The experiments were conducted using pure methane gas in a stirred cryogenic sapphire cell under isobaric condition (constant pressure), for pressure ranges of 50-300bar and using solutions of 25wt% MEG with 75wt% de-ionised Water. Experiments conducted using thermally exposed MEG to temperatures of 165°C, 180°C and 200°C for durations of 4 and 48h. The degradation products from these samples were then analysed by third party laboratories using two techniques: ion chromatography (IC) and high-performance liquid chromatography-mass spectroscopy (HPLC-MS). Results using both techniques showed that MEG was degraded when exposed to the above referenced temperatures and resulted in a formation of organic acids, such as glycolic, acetic, and formic acids. Another experimental study was conducted to study the kinetics of MEG hydrate inhibition for the binary CH4-H2O system. These experiments showed that difference between the hydrate start formation curve and the hydrate start dissociation curve (the metastable region) is narrow at lower pressures and that it widens as pressures increase. Similar trends were observed when the hydrate start formation and the hydrate end formation curves were compared. Evaluation of hydrate inhibition performance of the thermally degraded MEG samples established that all the samples resulted in increasing of hydrate formation temperatures. The findings of this study conclude that thermally exposed MEG causes a drop in hydrate inhibition performance due to thermal degradation effects.